Partisipasi Masyarakat Pada Kawasan Ekonomi Khusus (KEK) Pariwisata di Kecamatan Likupang Timur - Graseila Iyong; Ingerid Moniaga; Johansen Mandey (Sabua : Jurnal Lingkungan Binaan dan Arsitektur, 2021)
East Likupang District is designated as a Special Economic Zone (SEZ) for Tourism according to Government Regulation Number 84 of 2019 concerning the Likupang Special Economic Zone. However, the problem is that the citizen does not actively participate in the development process. The purpose of this study is to identify citizen participation and to analyze the relationship between the factors that influence citizen participation in the Tourism Special Economic Zone (SEZ) in East Likupang District. The analytical method used is the likert scale analysis and the chi square test. Likert scale analysis with manual calculations uses a formula to measure the opinion of each respondent about citizen participation in the development stage and the forms of participation given. Meanwhile, the chi square test is used to analyze the relationship between the factors that influence citizen participation with the help of SPSS. The results showed that the citizen was involved in the development stages from planning, implementation, monitoring to evaluation. However, the participation given is still not good in the aspects of involvement in meetings, giving ideas, energy, expertise and materials. In the development stage, citizen participation is influenced by external factors in the form of government and community groups but is not influenced by community leaders and internal factors. Meanwhile, forms of citizen participation are influenced by external factors in the form of government, community groups and community leaders as well as internal factors such as age and marital status but not influenced by gender, education level and type of work Keyword: Citizen Participation; Tourism SEZ; Likert Scale; Chi Square